The Role of Thoracic Medial Branch Blocks in Managing Chronic Mid and Upper Back Pain: A Randomized, Double-Blind, Active-Control Trial with a 2-Year Followup - Laxmaiah Manchikanti; Vijay Singh; Frank J. E. Falco; Kimberly A. Cash; Vidyasagar Pampati; Bert Fellows (Anesthesiology Research and Practice)
Study Design. A randomized, double-blind, active-control trial. Objective. To determine the clinical effectiveness of therapeutic thoracic facet joint nerve blocks with or without steroids in managing chronic mid back and upper back pain. Summary of Background Data. The prevalence of thoracic facet joint pain has been established as 34% to 42%. Multiple therapeutic techniques utilized in managing chronic thoracic pain of facet joint origin include medial branch blocks, radiofrequency neurotomy, and intraarticular injections. Methods. This randomized double-blind active controlled trial was performed in 100 patients with 50 patients in each group who received medial branch blocks with local anesthetic alone or local anesthetic and steroids. Outcome measures included the numeric rating scale (NRS), Oswestry Disability Index (ODI), opioid intake, and work status, at baseline, 3, 6, 12, 18, and 24 months. Results. Significant improvement with significant pain relief and functional status improvement of 50% or more were observed in 80% of the patients in Group I and 84% of the patients in Group II at 2-year followup. Conclusions. Therapeutic medial branch blocks of thoracic facets with or without steroids may provide a management option for chronic function-limiting thoracic pain of facet joint origin.